Cost-effectiveness of Direct Oral Anticoagulant vs. Warfarin Among Atrial Fibrillation Patients With Intermediate Stroke Risk - Choi, Ju Hee; Kim, Woojin; Kim, Yun Tae; Cho, Jaelim; Shin, Seung Yong; Kim, Changsoo; Kim, Jin-Bae (Frontiers in Cardiovascular Medicine, 2022)
Background Several studies have shown the cost-effectiveness of direct oral anticoagulants (DOACs), compared with warfarin, to prevent atrial fibrillation (AF) related complications. However, few have reported cost-effectiveness of DOACs in AF patients with intermediate stroke risk. Thus, we investigated the cost-effectiveness of DOACs vs. warfarin in non-valvular AF patients with intermediate stroke risk using national representative data. Methods We identified 7,954 newly diagnosed non-valvular AF patients (≥18 years) with intermediate stroke risk (CHA2DS2-VASc score: 1 for men and 2 for women) using the national healthcare utilization data from August 1, 2016, to July 31, 2019. Annual incidence rate of AF-related composite outcomes (heat failure, myocardial infarction, ischemic stroke, intracerebral hemorrhage, and gastrointestinal bleeding) was estimated. Cost-effectiveness was estimated using a Markov chain model with the transition probability of 1 year. The willingness-to-pay (WTP) was set at 32,000 per quality-adjusted life-year (QALY) gained. Results The total cost of warfarin, rivaroxaban, apixaban, dabigatran and edoxaban was 2,874, 5,761, 5,151, 5,761 and 5,851, respectively. The QALYs gained were 10.83, 10.95, 11.10, 10.49 and 10.99 years, respectively. The incremental cost-effectiveness ratio of rivaroxaban, apixaban, dabigatran and edoxaban was 29,743.99, 8,426.71, -8,483.04 and 18,483.55, respectively. The WTP was set at 32,000. DOACs (except dabigatran) were more cost-effective compared with warfarin because they did not exceed the WTP in the base-case analysis. Conclusion Our findings showed that DOACs were more cost-effective than warfarin in non-valvular AF patients with intermediate stroke risk.